New data on the calcareous plankton biostratigraphy of the middle-upper Miocene of the Mediterranean area - FORESI, L. M.; IACCARINO, S.; MAZZEI, R.; SALVATORINI, G. (1998)
The planktonic foraminifera of six sequences from middle to late Miocene are investigated. Five are located in the Mediterranean area and one in the Atlantic Ocean (Site 397). The aim of the research was to refine the biostratigraphy of the Serravallian to early Tortonian interval and to check the range of Neogloboquadrina acostaensis (Blow) and Paragloborotalia siakensis (Le Roy) which in the recent literature do have no more general consensus. The study of planktonic foraminifera allowed us to recognize a succession of events part of which are new in the Mediterranean area and document an overlap in the distribution of N. acostaensis and P.lia siakensis. Based on the new data, the zonal scheme of Iaccarino and Salvatorini (1982) and Iaccarino (1985) concerning the Serravallian to early Tortonian interval is emended. In particular it has been ascertained that the FO of N. acostaensis falls in the upper part of the Serravallian well before the LO of P.lia siakensis . The new zonation has been calibrated with the calcareous nannofossil zonation and the geomagnetic polarity time scale. In the light of the new data it is pointed out that in the Rio Castellania-Rio Mazzapiedi-Tortonian type-section the closest events to its base are the LO of P.lia siakensis, the FCO of N. acostaensis, and the FO of Discoaster hamatus. Therefore these events are reccomended in selecting the GSSP Serravallian/Tortonian boundary. Riassunto Sono state esaminate e/o riesaminate le associazioni a foraminiferi planctonici di sei sezioni mioceniche delle quali 5 nell' area mediterranea e una in Oceano Atlantico (Site 397) con lo scopo di migliorare le conoscenze biostratigrafiche dell'intervallo Serravalliano-Tortoniano inferiore ed in particolare di controllare le distribuzioni stratigrafiche di Neogloboquadrina acostaensis (Blow) e Paragloborotalia siakensis (Le Roy) sulle quali secondo i dati bibliografici pi recenti non esiste pi un generale consenso. Lo studio delle associazioni ha permesso di riconoscere una successione di eventi in ...